2013
DOI: 10.1038/labinvest.2013.114
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo signaling pathway is required for salivary gland development and its dysregulation is associated with Sjogren's syndrome

Abstract: Sjogren's syndrome (SS) is a complex autoimmune disease that primarily affects salivary and lacrimal glands and is associated with high morbidity. Although the prevailing dogma is that immune system pathology drives SS, increasing evidence points to structural defects, including defective E-cadherin adhesion, to be involved in its etiology. We have shown that E-cadherin plays pivotal roles in the development of the mouse salivary submandibular gland (SMG) by organizing apical-basal polarity in acinar and ducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
0
49
1
Order By: Relevance
“…3 and 4). Our results differ from previous studies, which found that E-cadherin organization was altered in SMG from NOD/ShiLtJ mice at embryonic stages and was lost in hMSG with SS (Enger et al 2013). This difference observed in NOD/ShiLtJ mice could be due to the use of mSMG at embryonic versus post-natal stages (Enger et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…3 and 4). Our results differ from previous studies, which found that E-cadherin organization was altered in SMG from NOD/ShiLtJ mice at embryonic stages and was lost in hMSG with SS (Enger et al 2013). This difference observed in NOD/ShiLtJ mice could be due to the use of mSMG at embryonic versus post-natal stages (Enger et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Depletion of LATS2 in ex vivo SMG cultures delocalizes TAZ, resulting in aberrant branching and inhibition of ductal extensions. The defects associated with LATS2 knockdown showed many similarities to phenotypes observed in human Sjogren's syndrome (Enger et al, 2013), an autoimmune disease of the salivary and lacrimal glands. Similar dysregulation of TAZ localization was confirmed in human Sjogren's syndrome tissues, indicating that dysregulated Hippo signaling might be a contributing factor in this disease.…”
Section: Salivary Glandsmentioning
confidence: 73%
“…These changes have recently been shown to rely on accurate Hippo pathway signaling (Enger et al, 2013). In particular, increases in TAZ/YAP levels, along with enhanced phospho-S89-TAZ levels, were found to be associated with the assembly of junctional E-cadherin/α-catenin complexes during SMG branching (Enger et al, 2013). Depletion of LATS2 in ex vivo SMG cultures delocalizes TAZ, resulting in aberrant branching and inhibition of ductal extensions.…”
Section: Salivary Glandsmentioning
confidence: 99%
“…Inhibiting ROCK, myosin II ATPase, or FAK also stalls branching after cleft initiation (Daley et al, 2009(Daley et al, , 2011. E-cadherin probably also plays a signaling role, as its association with the Hippo pathway effector TAZ (transcriptional co-activator with PDZ-binding motif) regulates branching of salivary explants (Enger et al, 2013).…”
Section: Matrix-driven Branchingmentioning
confidence: 99%